Narratives of exile and return: Francophone women’s identities in the aftermath of the 2011 Tunisian revolution - Pearson, Nicola (2016)
On 14th January 2011, President Ben Ali was forced to flee Tunis after twenty-three years in power. The revolution began in December 2010 with the self-immolation of Mohamed Bouazizi, a young fruit-seller who was acting in protest against the repressive and corrupt regime. The overthrow of the dictatorship went on to influence uprisings across the Arab world, and these became known in the West as the ‘Arab Spring’. Since 2011 Tunisia has witnessed a surge in creative production, and the role of art itself has been an important feature of the country’s political revolution. This thesis seeks to open up a new field by focusing on the literary output of two female travel writers of Tunisian origin, Colette Fellous and Dora Latiri, who both produced works of travel literature based on their journeys back to their homeland in the wake of the revolution. Fellous and Latiri have spent most of their adult lives living in Europe, having been exiled from Tunisia when they were young women. In Latiri’s 'Un amour de tn: Carnet d’un retour au pays natal après la revolution', photographs are woven into a fragmented and very personal narrative which highlights not only visions of contemporary Tunisia, but also the narrator’s difficult memories of her childhood. 'La Préparation de la vie' by Fellous similarly charts the narrator’s journey back to post-revolutionary Tunisia and brings to light the little-known phenomenon of the exile of Jewish communities from the country following the Arab-Israeli Six Day War in 1967. Both writers are haunted by feelings of dislocation from Tunisia yet seem compelled to keep returning to it.